Age and liver transplantation: a key factor in clinical outcomes? single center study in Argentina - Santillán Pazmiño, Marco; Arriola Benitez, Paula Constanza; Fernandez, Maria Florencia; Yantorno, Silvina; Descalzi, Valeria; Tarditti, Franco Daniel; Novellis, María Lucia; Fasolo, Juan Cruz; Rumbo, Martín; Tullius, Stefan Günther; Barros Schelotto, Pablo; Gondolesi, Gabriel Eduardo; et al. (Frontiers in Aging, 2025)
IntroductionGrowing demand for liver transplantation (LTx) has increased the use of elderly donors. In Argentina, however, data on the clinical impact of donor age on post-transplant outcomes remain limited.ObjectiveTo evaluate the effect of donor age on clinical, functional, and molecular outcomes after LTx at Hospital Universitario Fundación Favaloro Buenos Aires, Argentina.MethodsWe performed a retrospective cohort study of 494 LTx conducted between 2009 and 2020. Patients were stratified into two age groups: 18–59 years (Younger) and ≥60 years (Elderly). Overall and graft survival (OS and GS) were assessed using Kaplan–Meier and Cox regression analyses adjusted for recipient age, donor age, recipient gender, donor gender, transplant year, MELD score, disease etiology, donor BMI, DRI, CIT, WIT, Total Bilirubin (TBIL) and INR. Early postoperative complications including early allograft dysfunction (EAD) and early renal replacement therapy (RRT) were evaluated. Post-transplant liver function was assessed by routine biochemical tests. Gene expression of pro-inflammatory and senescence markers was quantified by qRT-PCR, and lipofuscin deposition was measured using ImageJ.ResultsAfter applying exclusion criteria, 267 LTx were included (Younger donors: n = 222; Elderly donors: n = 45). Recipients of elderly donor grafts showed significantly lower OS and GS (p < 0.05). In the multivariable analysis, donor age and TBIL remained independent predictors of GS, whereas donor age, recipient age, and TBIL were associated with OS. In contrast, neither the incidence of EAD nor early RRT differed between recipients of elderly versus young donor grafts. Early postoperative biochemical profiles were also similar between groups, with no significant differences in ALT, AST, ALP, or TBIL levels. Molecular analyses demonstrated that elderly donor livers exhibited significantly higher expressions of IL-1β, IL-6, TNF-α, p21 and CCND1, Elderly donor livers displayed higher baseline lipofuscin accumulation (p < 0.05), consistent with age-associated cellular senescence, and trends toward higher rejection rates.ConclusionDonor liver aging, characterized by increased inflammatory and senescence signatures, is associated with reduced patient and graft survival. These findings underscore the clinical relevance of considering donor biological age, beyond chronological age, in organ allocation and selection strategies.